If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 = 3(x + 0) Reorder the terms: 5 = 3(0 + x) Remove the zero: 5 = 3(x) Solving 5 = 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 5 + -3x = 3x + -3x Combine like terms: 3x + -3x = 0 5 + -3x = 0 Add '-5' to each side of the equation. 5 + -5 + -3x = 0 + -5 Combine like terms: 5 + -5 = 0 0 + -3x = 0 + -5 -3x = 0 + -5 Combine like terms: 0 + -5 = -5 -3x = -5 Divide each side by '-3'. x = 1.666666667 Simplifying x = 1.666666667
| 3(4x+3)(2x-5)=0 | | d-4(d+8)=-8 | | 3(4x-3)(2x-5)=0 | | 8/x=7/x-2 | | 35Q^2+33q+4=0 | | 13(x-9)=7x-10 | | 139=x+2x+(x+15) | | 11(x-2)=7x-11 | | 12x+13=7x+20 | | 32=x+x+(x+2)+(x+2) | | 50x^2-18x+6=0 | | 50x^2-18+6=0 | | 4xy+xy= | | 0.36(6)+0.06x=0.18(6+x) | | 1,006,458=x | | -18x=-13 | | 27=-5x | | 7.71=2(3.14)(x) | | 2x^2+17x-5=0 | | 4/3x^2+14/3x+2=0 | | 2x^2-17x-5=0 | | 2sin^2(x)+3sin(x)+1=0 | | -11t+16=-6 | | 9z+-12+-2z+5=0 | | 15p+3n-2m+10n= | | 9z-12-2z+15=0 | | 3x^2-30x+45=0 | | 4x^6+x^5-18x^4= | | x^2-44x=-c | | 15-6x=18-5x | | 4x^2-20x=24 | | 5m+3n-2m+10n= |